A Mini Review on Track-Etched Membranes Potential for Sensors Development - Sütekin, S.D.; Rakisheva, S.R.; Mashentseva, А. A.; Barsbay, M. (Karagandy University of the name of academician E.A. Buketov, 2025)
Track-etched membranes (TeMs) have emerged as a promising class of nanostructured materials for the development of advanced sensing platforms. Owing to their highly uniform pore architecture, controllable dimensions, and versatile surface chemistry, TeMs can be used to create highly sensitive, selective, and robust sensors. This review provides a comprehensive overview of recent advances in the use of TeMs for sensor development, with a particular emphasis on functionalization strategies and application domains. The review discusses stimuli-responsive TeMs in detail which are capable of dynamic switching in response to environmental triggers such as pH, temperature, light, or redox. Functional nanochannels engineered through various modifications, such as polymer grafting or metal-organic frameworks incorporation, exhibit unique ionic transport behaviors suitable for real-time detection and biomimetic sensing. TeMs have also shown considerable potential in the detection of toxic metal ions, where tailored chemical groups and hybrid interfaces enable sub-ppb sensitivity in complex matrices. Furthermore, their capacity to host biomolecules like DNA probes, antibodies, or enzymes opens avenues for biosensing applications, including clinical diagnostics, virus detection, and neurotransmitter detecting. Additionally, their integration into wearable devices highlights their potential for flexible, real-time health monitoring. Challenges related to large-scale manufacturing, long-term stability, and standardization remain and are addressed in this review. Looking forward, TeMs have potential to bridge the gap between lab-scale innovation and practical sensor technologies, offering solutions for environmental, biomedical, and industrial applications.
Keywords: track-etched membranes (TeMs); composite track-etched membranes (CTeMs); biosensors; hybrid membranes; functional nanomaterials; stimuli-responsive materials